2012
DOI: 10.1371/journal.pone.0042377
|View full text |Cite
|
Sign up to set email alerts
|

LncRNAs Expression Signatures of Renal Clear Cell Carcinoma Revealed by Microarray

Abstract: BackgroundLong noncoding RNAs (lncRNAs) are an important class of pervasive genes involved in a variety of biological functions. They are aberrantly expressed in many types of cancers. In this study, we described lncRNAs profiles in 6 pairs of human renal clear cell carcinoma (RCCC) and the corresponding adjacent nontumorous tissues (NT) by microarray.Methodology/Principal FindingsWith abundant and varied probes accounting 33,045 LncRNAs in our microarray, the number of lncRNAs that expressed at a certain leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
99
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(105 citation statements)
references
References 41 publications
5
99
1
Order By: Relevance
“…A previous study showed TRIM52-AS1 to be downregulated in RCC tissues, as determined by lncRNAs expression profiling (16,17). To confirm the result of sequencing, RT-qPCR was used to quantify the expression levels of TRIM52-AS1 in 60 matched RCC tissue samples and adjacent normal tissue samples.…”
Section: Trim52-as1 Is Downregulated In Rcc Tissues and Cell Linesmentioning
confidence: 98%
See 1 more Smart Citation
“…A previous study showed TRIM52-AS1 to be downregulated in RCC tissues, as determined by lncRNAs expression profiling (16,17). To confirm the result of sequencing, RT-qPCR was used to quantify the expression levels of TRIM52-AS1 in 60 matched RCC tissue samples and adjacent normal tissue samples.…”
Section: Trim52-as1 Is Downregulated In Rcc Tissues and Cell Linesmentioning
confidence: 98%
“…Previous sequencing for the expression of LncRNAs showed TRIM52-AS1 was downregulated in RCC (16,17). The present study was undertaken to verify the expression of TRIM52-AS1 in RCC, and to assess the impact of TRIM52-AS1 on cell proliferation, invasion and migration.…”
Section: Introductionmentioning
confidence: 94%
“…The differentially expressed mRNAs and lncRNAs were selected to construct the co-expression network as described in previous reports [36,37]. The network construction procedures included the following: (1) pre-processing data: for one mRNA with different transcripts, the median value was used to represent the gene expression, without special treatment for lncRNA expression values; (2) screening data: subsets of data were removed according to the lists of the differential expression of lncRNA and mRNA; (3) Pearson's correlation coefficient was calculated, and the P value was used to calculate the correlation coefficient between lncRNAs and mRNAs; and (4) screening based on Pearson's correlation coefficient: Pearson's correlation coefficients greater than 0.99 were considered meaningful and used to draw the lncRNA/mRNA co-expression network with the Cytoscape software (V2.8.3, http://www.cytoscape.org/) [38].…”
Section: Construction Of the Coding-non-coding Gene Co-expression Netmentioning
confidence: 99%
“…Using a range of techniques, such as microarray, 18 RNA sequencing, 19 and real-time PCR, 20 many studies have confirmed that lncRNA expression levels differ between normal and tumor tissues and vary among tumor types. [21][22][23] Although some of these abnormal expression patterns may be secondary effects from the cancer transformation, several factors suggest that lncRNAs could influence tumorigenesis. These factors include the tremendous complexity and diversity of the lncRNA landscape, the finding that lncRNAs are often located at crucial sites (eg, regions of singlenucleotide polymorphisms (SNPs), amplifications, or at common breakpoints), the presence of sequence motifs and other elements that result in specific structures, their regulation, and their functional relationships with other nucleic acids and proteins.…”
Section: Lncrnas In Cancermentioning
confidence: 99%